PELAKSANAAN KECERDASAN MAJEMUK DALAM MENGEMBANGKAN METODE MENGHAFAL ALQUR’AN PADA MADRASAH ALIYAH SWASTA TARBIYAH ISLAMIYAH KEC. HAMPARAN PERAK, KABUPATEN DELI SERDANG - Rangkuti, Charles; Ependi, Rustam; Amin, Nazrial (Scenario (Seminar of Social Sciences Engineering and Humaniora); 2023, 2023)
This Qur'an is a book that was revealed to be a guide for Muslims around the world, so that this Qur'an is not just a page that is studied. Because when reading the Qur'an can also get rewards for the reader and this Qur'an is a blajjah and helper when the day of charity reckoning arrives later. The Qur'an also describes a lot of knowledge, implied and penetrated knowledge. The Qur'an is also a mercy for the universe so that its contents are suitable and can be used as a guide for human life. In order to understand the contents of the Qur'an concretely, let alone the discussion of education, it must use tafsir. Memorizing the Qur'an is a process of inserting verses of the Qur'an into the heart and mind so that they are not lost again. In undergoing this process, huffaz (Qur'an memorizers) apply methods that may vary from one person to another. The choice of memorization method is usually adjusted to one's learning character. People with visual learning characters, for example, prefer to memorize the Qur'an by looking directly at the writing of Qur'an verses in the mushaf before finally memorizing them.